Development on Innovation Competency of Teaching Staff in Indian Universities: Fostering Innovation Competency in Higher Education Teaching Staff (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Higher education institutions in Deemed Universities in Maharashtra need to give proper attention to the growth of innovation skills of teaching staff in order to fulfill the ever-changing needs of students and society overall. Why are we concerned about innovation competence? Innovation is generally recognized as a central mechanism within an enterprise synonymous with transformation, because it allows the company to revitalize what it sells and how it produces and provides goods andor services. (Du Chatenier, 2011 Tidd, Bessant and Pavitt, 2001). Subsequently, people who can make a contribution to and participate in innovation are especially required in the various sectors of the labor market (Rasmussen 2009). Watts, Garcia-Carbonell Andreu-Andres put forward a detailed conceptualization of innovation 'innovation means different things to different people. It is, for some, the emergence of a novelty, something fundamentally new, a concept, a technique, a device, an invention. Among some, innovation is an advancement of something which already exists. For others, to be considered innovation, that something has to be useful to people or organizations and to meet their needs. In other words, innovation has an underlying social dimension that transcends mere invention or improvement of a product or process.